Tratamento da pornografia de vingança pelo judiciário maranhense: avaliando a atual divisão de competências entre Vara de Violência Doméstica e Familiar contra Mulher e Juizado Especial Criminal a partir do critério efetividade. - PINHEIRO, Rossana Barros (2018)
The pejorative exposition of female intimacy in a context of affective and or sexual relationships, revenge porn, is as a complex and frequent phenomenon in human relations of cyberculture. Aggravating the destructive consequences of violence, the present object of study has a juridical nature of gender, evidenced in the perception of all the different people involved it shows that the virtual instances are not separated from presential instances, because they often connected. Therefore, Brazilian Law 11,340 / 06, popularly known as the Maria da Penha Law, is the most appropriate the legal instrument for this crime, considering the transdisciplinary approach to gender and the criminalization of the different violations that may be perpetrated at this context. However, the jurisprudential perspective of the country, specially considering the Maranhão state Court, still reveals significant difficulties in approachins and consolidating the gender legal nature of the phenomenon, resulting on the dual division of competencies diametrically opposed for same crime. So, the present investigation analyzed the current division of competences of the Maranhão state to legal repression the revenge porn (understood sometimes as a crime of less offensive potential, sometimes as intrafamily violence against women), trying to subsidize more effective judicial protection. In the methodology, we chose bibliographic search, field search, systematic observation and focus group as well as be used content analysis to interpretation the data obtained.